Long-term Results of Drug and Interventional Treatment in Patients with Morphologically Verified Idiopathic Arrhythmias - O. V. Blagova; A. V. Nedostup; E. A. Kogan (Столичная издательская компания, 2021)
Aim. To study the late results of medical and interventional treatment in patients with morphologically verified nature of idiopathic arrhythmias.Methods. The prospective study included 20 patients (mean age 43.1±11.3 years, 10 female) with atrial fibrillation (AF), supraventricular and ventricular extrasystole, supraventricular and ventricular tachycardia, conduction disturbance without structural heart changes. In addition to the standard examination, the level of anti-heart antibodies was initially determined; endomyocardial biopsy (EMB) of the right ventricle with PCR study for the viral genome; DNA diagnostics (n=4), coronary angioraphy (n=6), skin biopsy (n=1) were performed. The median follow-up was 134 [128; 138] months.Results. By EMB in the initial examination were diagnosed: active (n=8)/borderline (n=3) infectious immune myocarditis; parvovirus-positive endomyocarditis (n=1); undifferentiated vasculitis (n=2); myocardial vasculitis (n=1); Fabry disease (n=1); arrhythmogenic right ventricular dysplasia (n=1); unspecified cardiomyopathy (n=2). Anti-heart antibodies were the most important in myocarditis diagnosis and monitoring. All patients with myocarditis/vasculitis (n=15) received its basic therapy: acyclovir (n=10); immunoglobulin G 10-12.5 g (n=2); hydroxychloroquine 200 mg/day (n=15); glucocorticoids (n=14); azathioprine 150 mg/day (n=2). The late results were evaluated in all patients with myocarditis. Initially, in 62.5% of patients a resistance of AF to all antiarrhythmic drugs was noted. After treatment the average frequency of AF paroxysms decreased (from 8 [5; 8] to 3 [1,25; 7,75] points). By the end of the follow-up, six patients underwent radiofrequency ablation (RFA) for AF, the full effect was achieved once. All patients without RFA have AF partially or completely resistant to drugs. Two patients (without RFA) died from ischemic stroke/ pulmonary embolism.Conclusion. Using EMB the causes of idiopathic arrhythmias (mainly AF) were diagnosed: immune inflammatory diseases in 75% and genetic in 25% of patients. As a result of complex treatment, the general burden of arrhythmias has decreased. But the presence of myocarditis and primary cardiomyopathy, without reducing the cardiac contractility and dilatation, does not allow achieving a stable antiarrhythmic effect. Lethality for 11 years was 10%. The causes of death were thromboembolic complications.